Two new species of the orb-weaving spider genus Alpaida (Araneae, Araneidae) from Peru - Deza, Mariajosé; Andía, Juan Manuel (Zootaxa, 2014)
Two new species of the orb-weaving spider genus Alpaida O. P.-Cambridge, 1889 are described and illustrated; Alpaida losamigos n. sp. based on females from Madre de Dios, and Alpaida penca n. sp. based on females and males from Cajamarca.